Effect of Recombinant Human Bone Morphogenetic Protein 2 Associated With a Variety of Bone Substitutes on Vertical Guided Bone Regeneration in Rabbit Calvarium. Issue 3 (1st March 2013) - Polo, Cristiane Ibanhes; Lima, Júlio Leonardo Oliveira; De Lucca, Leandro; Piacezzi, Christiano Borges; Naclério‐Homem, Maria da Graça; Arana‐Chavez, Victor Elias; Sendyk, Wilson Roberto
Abstract : Background: A major challenge for dental implantology is to consistently obtain appropriate bone augmentation before implant placement. The aim of this study is to evaluate the effect of recombinant human bone morphogenetic protein 2 (rhBMP‐2) associated with bone substitute materials beta‐tricalcium phosphate (β‐TCP), biphasic calcium phosphate (BCP), and bovine bone mineral on vertical guided bone regeneration (GBR) in rabbit calvarium. Methods: Four titanium cylinders were fixed to the calvarium of 22 rabbits. In group 1 (n = 10), three cylinders were randomly filled with one of the test materials, and one cylinder was filled with a blood clot (CL). In group 2 (n = 12), the cylinders were randomly assigned to the same materials and CL but with the addition of rhBMP‐2. Bone labels were injected over the course of 13 weeks, and euthanasia was performed 14 weeks after surgery in both groups. Results: The mean volume and area of tissue growth was greater in group 2 (with rhBMP‐2) than in group 1 (without rhBMP‐2), irrespective of the material used ( P <0.001). The mean volume of tissue growth in the CL cylinder was smaller than that observed with all other materials ( P <0.001) in both groups. The mean area of regenerated bone in the CL cylinder was smaller than that observed in the β‐TCP cylinder ( P = 0.028). The histologic study revealed more lamellar bone in the rhBMP‐2 group, with a greater level of biodegradation of all the bone substitute materials tested. Conclusion: The use of rhBMP‐2/absorbable collagen sponge (ACS) combined with all of the bone substitute materials tested resulted in a greater amount of bone formation than that produced with the bone substitute materials alone or rhBMP‐2/(ACS) and CL using the rabbit calvarium GBR model.